IL28B genotype is not useful for predicting treatment outcome in Asian chronic hepatitis B patients treated with pegylated interferon‐α. Issue 5 (25th April 2013) - Holmes, Jacinta A; Nguyen, Tin; Ratnam, Dilip; Heerasing, Neel M; Tehan, Jane V; Bonanzinga, Sara; Dev, Anouk; Bell, Sally; Pianko, Stephen; Chen, Robert; Visvanathan, Kumar; Hammond, Rachel; et al.
Abstract Background and Aim IL28B genotype predicts response to pegylated interferon (peg‐IFN)‐based therapy in chronic hepatitis C. However, the utility of IL28B genotyping in chronic hepatitis B (CHB) cohorts treated with peg‐IFN is unclear. It was investigated whether IL28B genotype is associated with peg‐IFN treatment outcomes in a predominantly Asian CHB cohort. Methods This was a retrospective analysis of CHB patients treated with 48 weeks of peg‐IFN monotherapy. IL28B genotype (rs12979860) was determined (TaqMan allelic discrimination kit). Baseline hepatitis B virus (HBV)‐DNA, alanine aminotransferase, and liver histology were available. The primary end‐points were HBV e antigen (HBeAg) seroconversion with HBV‐DNA < 2000 IU/mL 24 weeks post‐therapy (HBeAg‐positive patients) and HBV‐DNA < 2000 IU/mL 24 weeks after peg‐IFN (HBeAg‐negative patients). The association between IL28B genotype and peg‐IFN outcomes was analyzed. Results IL28B genotype was determined for 96 patients. Eighty‐eight percent were Asian, 62% were HBeAg positive, and 13% were METAVIR stage F3‐4. Median follow‐up time was 39.3 months. The majority of patients carried the CC IL28B genotype (84%). IL28B genotype did not differ according to HBeAg status. The primary end‐points were achieved in 27% of HBeAg‐positive and 61% of HBeAg‐negative patients. There was no association between IL28B genotype and the primary end‐point in either group. Furthermore, there was no difference in HBeAg loss alone, HBV surface antigen, alanine aminotransferase normalization, or on‐treatment HBV‐DNA levels according to IL28B genotype. Conclusions In the context of a small possible effect size and high frequency in Asian populations, IL28B genotyping is likely to have, at best, limited clinical utility for predicting peg‐IFN treatment outcome for CHB patients in the Asia–Pacific region.